Mississippi River tragedies : a century of unnatural disaster - Klein, Christine A., 1956-; Zellmer, Sandra Beth (New York : New York University Press, 2016)
American engineers have done astounding things to bend the Mississippi River to their will: forcing one of its tributaries to flow uphill, transforming over a thousand miles of roiling currents into a placid staircase of water, and wresting the lower half of the river apart from its floodplain. American law has aided and abetted these feats. But so-called 'natural disasters' continue to strike the Mississippi basin. In some places, only the tombstones remain, leaning at odd angles as the underlying soil erodes away. This book reveals that it is seductively deceptive - but horribly misleading - to call such catastrophes 'natural.' Klein and Zellmer present a sympathetic account of the human dreams, pride, and foibles that got us to this point, weaving together engaging historical narratives and accessible law stories drawn from actual courtroom dramas.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Flood control -- Mississippi River -- History; Floods -- Mississippi River Valley -- History; Hydraulic engineering -- Mississippi River Valley -- History; Floodplain management -- Government policy -- United States; Flood damage prevention -- Government policy -- United States; United States. -- Army. -- Corps of Engineers -- History; Society; United States of America, USA; History; History of the Americas; Social services & welfare, criminology; Conservation of the environment